Antioxidant Activity Test Of Methanol Extract Of Gaharu (Aquilaria Malaccensis Lam.) Bark With Dpph (1,1 Diphenyl-2-Picrylhydrazyl) Method - Ridwanto Ridwanto; Asep Trizaldi; Zulmai Rani; Anny Sartika Daulay; Haris Munandar Nasution; Dikki Miswanda (CV. Inara, 2023)
Gaharu (Aquilaria malaccensis Lam.) is one of the natural ingredients that can be used as an antioxidant. Antioxidants are compounds that can inhibit free radical reactions in the body. Free radicals have an impact on the pathogenesis of several diseases in humans due to oxidative stress in cells. The purpose of this study was to determine the class of secondary metabolites of agarwood bark and antioxidant activity and to compare the value of IC50 (Inhibitory concentrations) of the methanol extract of agarwood bark with the IC50 of vitamin C in the DPPH method using UV-Vis spectrophotometry. The methanol extract of agarwood bark was macerated using methanol, then determined the content of secondary metabolites of Simplicia. The determination of antioxidant activity was carried out on the methanol extract of agarwood bark with the addition of DPPH at various concentrations. The sample concentrations were 20, 40, 60, 80, and 100 µg/mL.. As a comparison, vitamin C was used with concentrations of 4, 8, 12, 16 and 20 µg/mL.. Then they calculated percent attenuation (% inhibition) and the value of IC50. The results of the screening on the methanol extract of agarwood bark contained chemical compounds such as flavonoids, saponins, and tannins. The determination of antioxidant activity was carried out using a UV-Vis spectrophotometer with the DDPH method. The results were obtained from the methanol extract of the bark of agarwood, which has antioxidant activity in the strong category with an IC50 value of 94.59 µg/mL.and vitamin C in the very strong category with an IC50 value of 22,11 µg/mL.